Dual antiplatelet therapy with ticagrelor vs clopidogrel in patients with TIA or minor stroke with or without symptomatic carotid artery stenosis: a post hoc analysis of the CHANCE-2 trial - Yongjun Wang; Yilong Wang; Xingquan Zhao; Jing Jing; Hao Li; Xia Meng; Anxin Wang; Yong Jiang; Jinxi Lin; Qin Xu; Xuewei Xie; Pan Chen (Stroke and Vascular Neurology)
Background and purpose Symptomatic internal carotid artery stenosis (sCAS) is an essential cause of transient ischaemic attack (TIA) or minor stroke. We aimed to evaluate whether the superiority of aspirin-ticagrelor over aspirin-clopidogrel varies between patients with sCAS or not.Methods This was a post-hoc analysis of the High-Risk Patients with Acute Nondisabling Cerebrovascular Events-II (CHANCE-2) trial, all of which were CYP2C19 loss-of-function alleles carriers. The primary exposures of interest were the treatment group and sCAS status. The primary efficacy endpoint was the new stroke assessed within 90 days.Results A total of 5920 (92.3%) from 6412 were analysed, including 197 (3.3%) with sCAS and 5723 (96.7%) without sCAS. Stroke recurrence occurred in 13 (12.15%) and 11 (12.22%) patients with sCAS who received aspirin-ticagrelor and aspirin-clopidogrel, respectively (adjusted HR, 1.04; 95% CI, 0.46 to 2.36; p=0.930). Among patients without sCAS, there were 158 cases (5.52%) of new strokes in the aspirin-ticagrelor group and 222 cases (7.76%) in the aspirin-clopidogrel group (HR, 0.70; 95% CI, 0.57 to 0.86; p=0.0006). The treatment-by-sCAS subtype was not significant (p=0.405).Conclusions Genotype-guided dual antiplatelet treatment with aspirin-ticagrelor may be beneficial for preventing recurrent strokes in patients without sCAS; however, it appears less effective in those with sCAS. No significant interaction was found between the treatment and sCAS subtypes.Trial registration number NCT04078737.